KEBIJAKAN EKONOMI SYARIAH MUHAMMADIYAH MELALUI PENDEKATAN ANALISIS SWOT DALAM PENGUATAN EKONOMI UMAT - Soraya Ayumara; Amir Mukadar; Marini Marini (UM. Bengkulu, 2024)
This study examines Muhammadiyah's sharia economic policy in the context of strengthening the ummah's economy through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. Muhammadiyah as the second largest Islamic mass organization in Indonesia has a strategic role in the development of the sharia economy through various economic charities such as the Sharia People's Financing Bank (BPRS), Baitul Mal wa Tamwil (BMT), sharia cooperatives, and the Muhammadiyah Amil Zakat Infak Sedekah Institution (LAZISMU). This qualitative-descriptive research uses secondary data sources in the form of Muhammadiyah policy documents, sharia economic regulations, official reports of organizations, and scientific literature. The results of the SWOT analysis show that the main strength of Muhammadiyah lies in its wide organizational network, high public trust, and commitment to Islamic economic principles. The main weaknesses include fragmentation of coordination between economic institutions, limited sharia economic literacy at the grassroots level, and lack of integration of the digital financial system. Significant opportunities arise from the growth of the national Islamic finance industry, government regulatory support, and increasing awareness of the people towards the halal economy. Threats include competition with other conventional and Islamic financial institutions, as well as global economic dynamics. The SWOT strategy matrix results in four policy orientations: the SO (aggressive-expansive) strategy, the WO (turnaround) strategy, the ST (diversification) strategy, and the WT (defensive) strategy. Policy implications include strengthening the integration of Muhammadiyah's sharia economic ecosystem, increasing the capacity of human resources, accelerating digital transformation, and strengthening the branding of the sharia economy based on progressive Islamic values. Keywords: Sharia Economy, Muhammadiyah, SWOT Analysis, Strengthening the People's Economy, Strategic Policies